1973
DOI: 10.1161/01.cir.48.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Dual A-V Nodal Pathways in Patients with Paroxysmal Supraventricular Tachycardia

Abstract: SUMMARYElectrophysiological evidence suggestive of dual atrioventricular (A-V) nodal pathways is presented in two patients with normal P-R interval and reentrant paroxysmal supraventricular tachycardia (PSVT). His bundle recordings and atrial stimulation were used to obtain this electrophysiological evidence. Recently reported studies in man suggest that A-V nodal reentrance is a common mechanism of paroxysmal supraventricular tachycardia (PSVT) .6-8 A-V nodal reentrance implies either the presence of dual A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
4

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(139 citation statements)
references
References 16 publications
4
131
0
4
Order By: Relevance
“…These fibers were under abnormal conditions of external potassium and catecholamine stimulation and the situation may not be clinically applicable in the absence of myocardial infarction. In any event, the clinical electrophysiologic division into ectopic versus re-entry mechanisms is useful in that it F[CURLE 6. Graph of the response of a re-entry supraventricular tachYcardia to progressively more premature stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…These fibers were under abnormal conditions of external potassium and catecholamine stimulation and the situation may not be clinically applicable in the absence of myocardial infarction. In any event, the clinical electrophysiologic division into ectopic versus re-entry mechanisms is useful in that it F[CURLE 6. Graph of the response of a re-entry supraventricular tachYcardia to progressively more premature stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying electrophysiological mechanism is the presence of a dual atrioventricular (AV) node physiology, including a fast and a slow pathway [1], characterized by different refractory periods. Dual AV node physiology is a frequent finding, being described in up to 90% of patients in a small case sample of heavily sedated patients undergoing electrophysiological study (EPS) [2], but does not always imply an AVNRT.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling intervals (A1A2 or V1V2) were progressively shortened until refractoriness of the atrium or ventricle occurred. The functional properties of the AV conduction system and initiation of PSVT were studied in all patients using different protocols of cardiac stimulation, which we numerically designated as methods [1][2][3][4][5][6] as follows: 1) Premature stimulation from atrium (A2) with the basic cycle length (BCL) consisting of atrial pacing alone.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to induce PSVT in patients [4][5][6] with both methods 1 and 2 when comparable ant SH delays were achieved indicates that effect of method 2 on ret AV nodal pathways was not sufficient to prevent PSVT. Also, direct comparison of ret AV nodal conduction times (H2-A2 intervals) with methods 5 and 6 showed that simultaneous AV stimulation did not significantly affect the H,A2 intervals except in patient 1.…”
Section: Definition Of Termsmentioning
confidence: 98%
See 1 more Smart Citation